2022
DOI: 10.3389/fimmu.2022.900284
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic Subsets Impact Cerebral Cortex and Cognition: Differences Between Healthy Subjects and Patients With First-Episode Schizophrenia

Abstract: Monocytes are a highly heterogeneous population subcategorized into classical, intermediate and nonclassical subsets. How monocytes and their subsets may shape brain structures and functions in schizophrenia remains unclear. The primary goal of this cross-sectional study was to investigate monocytic subsets and their specific signature genes in regulation of cerebral cortical thickness and cognitive functions in first-episode schizophrenia (FES) patients. Whole-blood RNA sequencing of 128 FES patients and 111 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…We previously found that some FES patients had higher stress sensitivity ( Xuan et al, 2022 ) and reduced amounts of nonclassical monocytes along with altered signature gene expressions ( Chen et al, 2022 ) compared to HCs, implying their deficits in myeloid reprogramming. To relate the implications of repMg to a clinical setting, we explored a cohort from these FES patients and HCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously found that some FES patients had higher stress sensitivity ( Xuan et al, 2022 ) and reduced amounts of nonclassical monocytes along with altered signature gene expressions ( Chen et al, 2022 ) compared to HCs, implying their deficits in myeloid reprogramming. To relate the implications of repMg to a clinical setting, we explored a cohort from these FES patients and HCs.…”
Section: Resultsmentioning
confidence: 99%
“…After a week of transfer adaptation, the mice were subject to CUS/Ctr and CSF1Ri/Veh treatments ( Figure 1A and Supplementary Figure S2B ). CUS procedures, as previously described ( Cangalaya et al, 2020 ; Chen et al, 2022 ; Xuan et al, 2022 ), were followed. Briefly, mice were exposed to a variable sequence of seven mild and unpredictable stressors once per day (d) for eight consecutive weeks, including food and water deprivation overnight, rat odor and isolation overnight, restraint in a 50-ml tube for 2 h, wet bedding and tilted cage, stroboscopic illumination overnight, flipped light/dark exposure, and swimming at 18°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the activation of monocytes has been consistently reported in schizophrenia, and first-episode schizophrenia had higher MCP-1 (Monocyte chemoattractant protein-1) both in the cerebrospinal fluid and blood [ 57 ]. Moreover, a recent study demonstrated atypical monocyte genes were negative correlated with cortical thickness and cognitive function in healthy controls, however, the correlation was attenuated in schizophrenia [ 58 ], highlighting the importance to explore monocyte subsets in the deterioration of cognitive function after ECT. Moreover, since peripheral systemic inflammation can lead to microglia activation in the brain, in vivo assessment of microglia activity before and after ECT by 18-kDa translocator protein (TSPO) PET can help to further clarify whether ECT treats schizophrenia by reducing neuroinflammation [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes with CD16 + are generally elevated in a variety of diseases, including obesity, diabetes mellitus, cardiovascular disease, trauma, sepsis, autoimmunity, and psychosis ( 9 , 14 ). The precise onset of sepsis in obese patients with diabetes ( 5 ) is challenging, since we lack an understanding of the pathogenic mechanisms driving sepsis ( 15 ).…”
Section: Introductionmentioning
confidence: 99%